Learning Module on Buffer Material with a CRT Approach to Solve Problem Topics in Jombang Typical Coffee Beer-Drink - Dei Gratia Kanthi Nabella; I Gusti Made Sanjaya; Suyatno Suyatno (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Learning with the CRT approach is suitable for realizing contextual learning in the Independent Curriculum. So, research was carried out to develop a PBL model learning module using a CRT approach that is ideal for application in teaching chemistry regarding buffer solutions. Method: The research carried out was of a qualitative descriptive type. Open module development uses the Research and Development (R&D) method. The research stages include definition, design, development, and dissemination. Results: The trial of the teaching application module was carried out at 3rd State Senior High School Jombang. The results show that the Learning module developed is suitable for learning Buffer material using the CRT approach, which is indicated by a validity score of 4 in the outstanding category and can complete 35 students with an average increase in learning outcomes in the N-Gain score in the medium category. Novelty: The novelty of this research lies in the CRT approach, which is essential to apply to the independent curriculum combined with the PBL learning model to train students to analyze a problem in a buffer material.